Malarial hepatitis and renal failure: a study of two cases (Italian Journal of Public Health, 2011)
We report two cases of severe malaria who presented with non-specific clinical features. One of the casesis a 50 year old female who was brought to our hospital with high grade fever and severe abdominal pain,whereas the other case was a 20 year old male presented with high grade fever and headache. Both thecases presented with abnormal liver and renal function tests. P.malariae and P.falciparum are responsiblefor clinically important renal disease the former causes chronic progressive syndrome and the latter causesacute renal disease. Severe malaria may present with non specific clinical features making it difficult todistinguish from other febrile illness.
Keywords: Plasmodium falciparum malaria; acute renal failure; fulminant hepatic failure